2023
DOI: 10.1097/mcp.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Home monitoring of coronavirus disease 2019 patients in different phases of disease

Abstract: Purpose of reviewVarious home monitoring programs have emerged through the COVID-19 pandemic in different phases of COVID-19 disease. Recent findingsThe prehospital monitoring of COVID-19-positive patients detects early deterioration. Hospital care at home provides early discharge with oxygen to empty hospital beds for other patients. Home monitoring during recovery can be used for rehabilitation and detection of potential relapses. General goals of home monitoring in COVID-19 are early detection of deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…As in other studies, patients admitted to the virtual ward had lower rates of comorbidity (see, eg, the review for the virtual ward COVID-19 by Majoor and Vorselaars 16 ). While recent literature reviews found a lower rate of readmission in older patients with COPD 3 and COVID-19 patients 17 after hospitalisation at home and virtual wards, the present study did not find any significant difference, as also reported in Creavin et al 5 However, readmission rates for all patients (hospital and virtual wards) increased if a patient was from a virtual ward, older and had COPD.…”
Section: Discussionsupporting
confidence: 58%
“…As in other studies, patients admitted to the virtual ward had lower rates of comorbidity (see, eg, the review for the virtual ward COVID-19 by Majoor and Vorselaars 16 ). While recent literature reviews found a lower rate of readmission in older patients with COPD 3 and COVID-19 patients 17 after hospitalisation at home and virtual wards, the present study did not find any significant difference, as also reported in Creavin et al 5 However, readmission rates for all patients (hospital and virtual wards) increased if a patient was from a virtual ward, older and had COPD.…”
Section: Discussionsupporting
confidence: 58%
“…At the Mayo Clinic, the home monitoring system for high-risk patients showed comparable efficacy with a reduced hospitalization ratio (13.7 vs. 18%) and lower mortality (0.5 vs. 1.7%) [ 21 ]. A recent review is available on remote monitoring of COVID-19 patients [ 22 ]. Because the late management of patients with asymptomatic hypoxemia led to a very poor outcome [ 2 ], meticulous screening using home oximetry with virtual monitoring could prevent hospitalization, resuscitation, and/or death [ 3 , 23 ].…”
Section: Discussionmentioning
confidence: 99%